Non‐invasive diagnostic imaging tests largely underdiagnose cardiac cirrhosis in patients undergoing advanced therapy evaluation: How can we identify the high‐risk patient?. Issue 6 (25th April 2021) - Belzile, David; Turgeon, Pierre Yves; Leblanc, Evelyne; Massot, Montse; Bourgault, Christine; Morin, Joёlle; Dupuis, Céline; Bilodeau, Marc; Laflamme, Maxime; Charbonneau, Eric; Trahan, Sylvain; Pagé, Sylvain; et al.
Abstract: Background: Patients with liver cirrhosis are generally considered ineligible for isolated cardiac transplantation or left ventricular assist device (LVAD) implantation. The aim of this retrospective study is to explore the diagnostic value of abdominal ultrasound, computed tomography scan (CT scan) and liver‐spleen scintigraphy to detect the presence of cirrhosis in patients with advanced heart failure. Methods: Among 567 consecutive patients who underwent pre‐transplantation or LVAD evaluation, 54 had a liver biopsy to rule out cardiac cirrhosis; we compared the biopsy results with the imaging investigations. Results: In about 26% ( n  = 14) of patients undergoing liver biopsy, histopathological evaluation identified cirrhosis. The respective sensitivity of abdominal ultrasound, CT scan and liver‐spleen scintigraphy to detect cirrhosis was 57% [29–82], 50% [16–84], and 25% [3–65]. The specificity was 80% [64–91], 89% [72–98], and 44% [20–70], respectively. Conclusion: Ultrasonography has the best‐combined sensitivity and specificity for the diagnosis of cirrhosis. However, more than a third of patients with cirrhosis will go undiagnosed by conventional imaging. As liver biopsy is associated with a low rate of complication, it should be considered in patients with a high‐risk of cirrhosis or with evidence of portal hypertension to assess their eligibility for heart transplantation or LVAD implantation.